Poly(lactic-co-glycolic acid) and atelocollagen hybrid scaffold seeded with annulus fibrosus cells enhances the formation of cartilaginous tissue engineered construct in vitro - Mohamad, Mohd Yusof; Mohamed Amin, Muhammad Azri Ifwat; Zulkifly, Ahmad Hafiz; Sha'ban, Munirah (IIUM, 2016)
Purpose: To evaluate the in vitro formation of 3D tissue engineered constructs (TECs) using rabbits’ annulus fibrosus (AF) cells seeded on poly(lactic-co-glycolic acid) (PLGA) based scaffolds.